PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH ASURANSI JIWA PADA MASA PANDEMI COVID-19 (STUDI KASUS PT ASURANSI JIWA SYARIAH BUMI PUTERA CABANG MEDAN) - Dita Marisa; Tuti Anggraini; Rahmi Syahriza (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine the effect of service quality on life insurance customer satisfaction during the Covid-19 pandemic (a case study of PT Asuransi Jiwa Syariah Bumiputera Medan Branch), with a sample size of 88 customers. The type of data used in this research is quantitative data. The data collection technique used is through a questionnaire. Analysis prerequisite tests include normality test, multicollinearity test, and heteroscedasticity test. Data analysis techniques using the t test, f test, multiple linear regression and test the coefficient of determination.The results showed that (1) there was a positive and significant effect of Tangible indicators on Customer Satisfaction of Life Insurance PT Asuransi Jiwa Syariah Bumiputera Medan Branch of 29.2%, (2) there was a positive and significant effect of Guarantee indicators on Customer Satisfaction of Life Insurance of PT Asuransi Jiwa Bumiputera Sharia Medan Branch of 37.9%, (3) there is a positive and significant effect of the Empaty indicator on Life Insurance Customer Satisfaction PT Asuransi Jiwa Syariah Bumiputera Medan Branch of 33.8%, (4) no significant effect on the Reliability indicator on Customer Satisfaction Life Insurance PT Asuransi Jiwa Syariah Bumiputera Medan Branch of -0.99%, (5) does not significantly influence the response indicator to Customer Satisfaction Life Insurance PT Asuransi Jiwa Syariah Bumiputera Medan Branch -0.33% (6) there is a positive and significant influence Tangible Evidence, Reliability, Response, Guarantee, and Empathy for Life Insurance Customer Satisfaction During the Covid-19 Pandemic PT Asuransi Jiwa Syariah Bumiputera Medan Branch with Fhitung 34,901.